PENGGUNAAN OBAT TRADISIONAL OLEH MASYARAKAT - Anggraini, Herlina (Politeknik Tiara Bunda, 2021)
Traditional medicines are the ingredients or the concoction of ingredients derived from plants, animals, minerals, galenic preparations or mixtures of these ingredients that have been used from generation to generation for treatment in accordance with the prevailing norms in society. This research aims to describe the use of traditional medicine by the people at District of Limo. This research is a descriptive research. The research design used cross sectional and a questionnaire as a measuring tool. The quantity of samples in this reseach was 74 people with purposive sampling technique and analyzed by univariate. The results of the analysis are in the form of a frequency distribution and proportion, in the form of table with its discussion. The results of this research showed that the most used types of traditional medicine were Standardized Herbal Medicines amounting to 87 people (58.8%), the type of treated disease was catch a cold amounting to 37 people (25.5%), the purpose of using traditional medicine was to treat minor ailments amounting to 51 people (37.0%), the reason for using traditional medicine was suitable and can be considered cured amounting to 54 people (36.5%), the source of information on traditional medicine was the family amounting to 59 people (45.1%), the way to get traditional medicine was the nearest kiosk amounting to 66 people (52.4%), the form of traditional medicine preparation was a liquid amounting to 65 people (62.5%), the way to use traditional medicine was to drink amounting 74 people (100%), the length of time in using traditional medicine was until people cured amounting to 58 people (62.4%) and the side effect of traditional medicine was that there were no side effects amounting to 7 people (78.6%)